Bladder exstrophy spica new design - Basem A. AbouWarda,; Wael El-Adl,; A. M. Saied,; Khaled M Zaghloul, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Bladder exstrophy such a congenital malformation of musculoskeletal, urogenital systems extending superficially to the anterior abdominal wall with the bladder being exposed, with incidence of 1:30000 in classic bladder exstrophy Methods: 18 children were included in this case series, 21 osteotomy assisted closure utilizing Sponseller’s osteotomy were done, then immobilized in newly designed -KZ- spica cast for 4-6 weeks period. Results: 18 patients who underwent 21 osteotomy assisted closure of exstrophy, 7 girls 33.33% and 14 boy 66.67% (chart 1), age of patients at time of intervention varied from 3 months to the age of 25 months, follow up period up to 3 years in some cases, on 14th day post-operatively ensuring complete closure of urological wound then at 4 and 6 weeks for cast removal after bony union Spica cast success was to achieve bony healing in appropriate time of 4-6 weeks post-osteotomy without delayed or non-union, Success rate of spica cast to achieve bony healing was 100%, with minimal skin rash as a complication